Perilaku Krom Dalam Limbah Cair Penyamakan Kombinasi Krom-Gambir dan Krom-Mimosa Pada Penyamakan Kulit - Ardinal Ardinal; Salmariza Salmariza; Anwar Kasim (Jurnal Litbang Industri, 2014)
This study aims to determine the amount of chrome that come out together with tannery waste in a tanned combination process of chrome-gambier and chrome-mimosa. the process research performed by 2 stages. The 1st stage  using chrome with 5 concentration,    they were 2,4,6 and 8 %. Then it followed by the 2nd stage  tanning process by using vegetable tanning, gambier and mimosa, with each 7% and 9% concentration. The results showed that the combination of chrome-gambier tanned at the same concentration disposed chromium waste less than the combination of chrome-mimosa tanned. The lowest total chrome waste on the chrome-gambier tanning combination was 3.9 ppm at  2% chromium and 7% gambier concentration and the highest was 146.6 ppm at 8% chromium and 9% gambier concentrations.  The lowest total chrome waste on the combination of chrome-mimosa tanning was 2.2 ppm at  2% chromium and 7% mimosa concentration and the highest was 170.4 ppm at 8 % chromium and 9% mimosa concentration. The 2ndtanning, was combination tanning process, chrome-gambier able to reduce chromium levels more than the chrome-mimosa tanning.ABSTRAKPenelitian ini bertujuan untuk mengetahui jumlah krom yang ikut terbuang bersama limbah proses penyamakan kulit yang di samak kombinasi krom-gambir dan krom-mimosa. Pelaksanaan penelitian proses penyamakan kulit  dilakukan dengan 2 tahap. Tahap I menggunakan krom dengan 5 variasi  konsentrasi yaitu 2, 4, 6 dan 8%. Setelah penyamakan tahap I kemudian dilanjutkan penyamakan tahap II dengan menggunakan penyamakan nabati, gambir dan mimosa, dengan variasi konsentrasi masing-masing 7 dan 9%. Hasil penelitian menunjukkan bahwa perlakuan penyamakan kombinasi krom-gambir pada konsentrasi yang sama menghasilkan limbah krom yang lebih sedikit dibandingkan dengan samak kombinasi krom-mimosa. Jumlah limbah krom pada penyamak kombinasi krom-gambir terendah adalah 3,9 ppm pada konsentrasi krom 2% dan gambir 7% dan tertinggi 146,6 ppm pada konsentasi krom 8% dan gambir 9%. Jumlah limbah krom pada penyamak kombinasi krom-mimosa terendah adalah 2,2 ppm pada konsentrasi krom 2% dan mimosa 7% dan tertinggi 170,4 ppm pada konsentasi krom 8% dan mimosa 9%. Penyamakan tahap II, yang merupakan samak kombinasi, krom-gambir dapat menurunkan kadar krom lebih banyak dibandingkan kombinasi krom-mimosa.